Impact of OTT Platforms on Mental Health: A SWOT Analysis - Kumar, Ashish; Verma, Amit (Indian Journal of Community Health, 2024)
Over-The-Top (OTT) platforms have seen a significant rise in popularity, especially during the COVID-19 pandemic. They offer convenience and a vast array of content, but their impact on mental health presents a complex picture. This SWOT analysis explores the strengths, weaknesses, opportunities, and threats of OTT platforms in relation to mental health. The proliferation of digital streaming services has redefined entertainment consumption patterns, presenting both opportunities and challenges for societal norms and individual well-being. Through a multidimensional analysis, this study investigates the evolving dynamics of Indian culture in the context of OTT content, examining how it shapes societal values, interpersonal relationships, and traditional norms. Furthermore, the paper scrutinizes the potential effects of OTT content on mental health, considering factors such as content diversity, representation, and the psychological implications of binge-watching.